An alternative for urine cultures: Direct identification of uropathogens from urine by MALDI-TOF MS - ALTINKANAT GELMEZ, GÜLŞEN; AKSU, MEHMET BURAK; İLKİ, ZEYNEP ARZU (AKADEMIAI KIADO ZRT, 2020)
Urinary tract infections are one of the most common bacterial infections and rapid diagnosis of the infection is essential for appropriate antibiotic therapy. The goal of our study was to identify urinary pathogens directly by MALDI-TOF MS and to perform antibiotic susceptibility tests in order to shorten the period spent for culturing. Urine samples submitted for culture to the Clinical Microbiology Laboratory were enrolled in this study. Urine samples were screened for leukocyte and bacteria amount by flow cytometry. Samples with bacterial load of 10(6)-10(7)/mL were tested directly by MALDI-TOF MS and antibiotic susceptibility tests (AST) were performed. In total, 538 positive urine samples were evaluated in our study. MALDI-TOF MS identified the microorganism directly from the urine sample in 91.8% of these samples and the concordance rate of conventional identification and direct detection was 95.8% for Gram-negatives at the genus and species level. Escherichia coli (n:401) was the most frequently isolated microorganism, followed by Klebsiella pneumoniae (n:57). AST results were generated for 111 of these urine samples and the concordance was 90% and 87% for E. coli and K. pneumoniae, respectively. Our results showed that screening of urine samples with flow cytometry to detect positive samples and identification of uropathogens directly by MALDI-TOF MS with an accuracy of over 90% can be a suitable method particularly for Gram-negative bacteria in clinical microbiology laboratories.
Keywords: Urine; direct identification; flow cytometry; MALDI TOF MS; DESORPTION IONIZATION-TIME; FLIGHT MASS-SPECTROMETRY; TRACT PATHOGENS; SAMPLES; BACTERIURIA